2001
DOI: 10.1073/pnas.221596698
|View full text |Cite
|
Sign up to set email alerts
|

A trithorax-group complex purified from Saccharomyces cerevisiae is required for methylation of histone H3

Abstract: Histone methylation has emerged as an important mechanism for regulating the transcriptional accessibility of chromatin. Several methyltransferases have been shown to target histone aminoterminal tails and mark nucleosomes associated with either euchromatic or heterochromatic states. However, the biochemical machinery responsible for regulating histone methylation and integrating it with other cellular events has not been well characterized. We report here the purification, molecular identification, and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
277
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(291 citation statements)
references
References 47 publications
13
277
1
Order By: Relevance
“…RBBP5 and WDR5, along with ASH2L, interact with the SET domain of MLL. This binding is also observed in other Set1 complexes and is required for the histone methyltranferase activity [Nagy et al, 2002]. It is of interest that a close MLL homolog, MLL2, was also shown to interact with ASH2L, RBBP5, and WDR5.…”
Section: The Story Is Two Complexmentioning
confidence: 74%
See 1 more Smart Citation
“…RBBP5 and WDR5, along with ASH2L, interact with the SET domain of MLL. This binding is also observed in other Set1 complexes and is required for the histone methyltranferase activity [Nagy et al, 2002]. It is of interest that a close MLL homolog, MLL2, was also shown to interact with ASH2L, RBBP5, and WDR5.…”
Section: The Story Is Two Complexmentioning
confidence: 74%
“…The Set1 protein contains a SET domain, which is highly homologous to the SET domain of MLL. Interestingly, just like the MLL protein, the Set1 complex was shown to methylate lysine 4 on histone H3 [Nagy et al, 2002]. This purified MLL complex is able to perform chromatin remodeling, histone methylation, acetylation, and deacetylation suggesting that all the associated proteins retain their enzymatic activities [Nakamura et al, 2002].…”
Section: The Story Is Two Complexmentioning
confidence: 99%
“…The first H3K4 methylase complex, COMPASS, was identified in the yeast S. cerevisiae and consists of Set1/KMT2 and seven other polypeptides (named Cps60-Cps15) [24]. Set1/KMT2 alone is not enzymatically active, but functions within COMPASS and is capable of mono-, di-, and trimethylating H3K4 [6,8,10,[24][25][26][27]. Following the identification of Set1/COMPASS as an H3K4 methylase, it was demonstrated that its mammalian homologues, the MLL proteins, MLL1-4 and hSet1A and B, are found in COMPASS-like complexes capable of methylating the fourth lysine of histone H3 [6,28,29] (Figure 2).…”
Section: Enzymatic Machinery Required For H3k4 Methylationmentioning
confidence: 99%
“…Thus, overexpressed p52 and Hut-78 induce MMP9 expression by tethering a H3K4 HMT complex. Whereas one multi-subunit complex (referred to as COMPASS and Set1 complex) that includes the Drosophila trithorax-related protein Set1 has been shown to trigger the mono-, di-and trimethylation of histone H3K4 in yeast (Briggs et al, 2001;Miller et al, 2001;Nagy et al, 2002;Noma and Grewal, 2002), multiple complexes harbouring robust H3K4 HMT activities have been isolated in mammalian cells and all of them contained one or two SET domain-containing homologues of yeast Set1 (Hughes et al, 2004;Glaser et al, 2006). As those distinct Set-1-like human H3K4 HMT complexes also share common subunits such as ASH2L, RBBP5 and WDR5, we determined whether those proteins interact with p52 by coimmunoprecipitation experiments.…”
Section: Rhd Nls Grr Ankyrin P65mentioning
confidence: 99%